Stimulation of Hyphal Ramification and Sporulation in Funneliformis mosseae by Root Extracts Is Host Phosphorous Status-Dependent - Xueguang Sun; Jingwei Feng; Jing Shi (Journal of Fungi, 2022)
A simulation of the environment inhabited by arbuscular mycorrhizal (AM) fungi could provide clues as to how to cultivate these obligate biotrophs axenically. Host intraradical and rhizospheric environments, root extracts and exudates in particular, would be crucial for AM fungi to complete their life cycles. In this study, we analyzed and compared the effects of root exudates (RE) and root extracts (RET) of white clover (Trifolium repens) on the asymbiotic growth of the AM fungus Funneliformis mosseae in vitro, and furtherly analyzed the chemical components of different RET with the LC-MS/MS technique in order to establish an asymbiotic cultivation system for this important and hardly domesticated AM fungus. RET is superior to RE in stimulating spore germination, hyphal elongation and branching, and secondary spore formation (p < 0.05). RET-induced effects were dependent on phosphate supplement levels, and the RET obtained following the treatment with low levels of phosphorus significantly promoted hyphal growth and sporulation (p < 0.05). A few newly formed secondary spores showed limited colonization of white clover roots. The low phosphorus-induced effects could be ascribed to the metabolic adjustment (mainly lipids and organic acids) of white clover roots under low phosphate conditions. Our findings demonstrate that the low phosphate-induced RET boosts the asymbiotic growth of AM fungus, and thus offers an alternative way to fulfill the life cycle of AM fungi asymbiotically.